(w+2)(2w-1)=0

Simple and best practice solution for (w+2)(2w-1)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (w+2)(2w-1)=0 equation:


Simplifying
(w + 2)(2w + -1) = 0

Reorder the terms:
(2 + w)(2w + -1) = 0

Reorder the terms:
(2 + w)(-1 + 2w) = 0

Multiply (2 + w) * (-1 + 2w)
(2(-1 + 2w) + w(-1 + 2w)) = 0
((-1 * 2 + 2w * 2) + w(-1 + 2w)) = 0
((-2 + 4w) + w(-1 + 2w)) = 0
(-2 + 4w + (-1 * w + 2w * w)) = 0
(-2 + 4w + (-1w + 2w2)) = 0

Combine like terms: 4w + -1w = 3w
(-2 + 3w + 2w2) = 0

Solving
-2 + 3w + 2w2 = 0

Solving for variable 'w'.

Factor a trinomial.
(-2 + -1w)(1 + -2w) = 0

Subproblem 1

Set the factor '(-2 + -1w)' equal to zero and attempt to solve: Simplifying -2 + -1w = 0 Solving -2 + -1w = 0 Move all terms containing w to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -1w = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -1w = 0 + 2 -1w = 0 + 2 Combine like terms: 0 + 2 = 2 -1w = 2 Divide each side by '-1'. w = -2 Simplifying w = -2

Subproblem 2

Set the factor '(1 + -2w)' equal to zero and attempt to solve: Simplifying 1 + -2w = 0 Solving 1 + -2w = 0 Move all terms containing w to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -2w = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -2w = 0 + -1 -2w = 0 + -1 Combine like terms: 0 + -1 = -1 -2w = -1 Divide each side by '-2'. w = 0.5 Simplifying w = 0.5

Solution

w = {-2, 0.5}

See similar equations:

| 2*8+3*-9= | | 3.45*4-8.18= | | 8m-5=(3m+5) | | 3.45(4)-8.18(1)= | | 3+3*6+2=-17 | | 500*98+x*0=(500+x)*30 | | 6n+3-5=-1 | | 6y+814=1186 | | cos(20)=(9/x) | | 32/-7 | | 4(1/4) | | 3x+10y=-15 | | F^2-22f+72=0 | | (5-8w)(5+8w)= | | 12-9y=-5 | | -7x+6-9=29 | | -4+3=-12+17x | | 3z/10-5=8 | | 5(2b-3)=3(b+9) | | 12(12n)+n-3=396 | | 1/8-X/7=3/56 | | F^2-22f=72 | | -4(1-7z)=-29 | | 5x-2/3=-49/10 | | 15x^4-15x^3=0 | | Z/7-2=6 | | f(x)=x^4+32 | | 8(p-a)-6=2(ap-5) | | 6x+7y(2-3y)=-21 | | 24x+9=21 | | 5x-7=4x-7 | | x/9-9=9 |

Equations solver categories